A nonparametric approach to understanding poverty in the Philippines: Evidence from the Family Income and Expenditure Survey. Issue 3 (19th August 2022) - Rivera, John Paolo Rosales
Abstract: Determining the poverty threshold using a meaningful measure is complex. In this study, we deviated from usual techniques. Instead, we employed a nonparametric approach in conducting a comparative analysis. Using the Philippine Family Income and Expenditure Survey, we estimated national and regional Epanechnikov kernel densities to understand how poverty evolved from 2000 to 2015. Results indicated that improvements in Philippine poverty incidence are attributable to various government poverty alleviation programs and to improvements in the country's economic performance. The consolidated picture of poverty generated prompted a pluralistic approach to poverty alleviation such as attention on agricultural reform and rural development; national industrialization policy; supportive trade, financial, and investment policies; and robust social protection policies. All of which require stakeholder coordination. Resumen: Determinar el umbral de pobreza usando una medida significativa es complejo. En este estudio, nos desviamos de las técnicas habituales. En su lugar, empleamos un enfoque no paramétrico al realizar un análisis comparativo. Utilizando la Encuesta de ingresos y gastos familiares de Filipinas, estimamos las densidades del núcleo de Epanechnikov nacionales y regionales para comprender cómo evolucionó la pobreza entre 2000 y 2015. Los resultados indicaron que las mejoras en la incidencia de la pobreza en Filipinas son atribuibles a varios programas gubernamentales de alivio de la pobreza y a mejoras en la economía del país. actuación. La imagen consolidada de la pobreza generada impulsó un enfoque pluralista del alivio de la pobreza, como la atención a la reforma agrícola y el desarrollo rural; política nacional de industrialización; políticas comerciales, financieras y de inversión de apoyo; y políticas sólidas de protección social. Todo lo cual requiere la coordinación de las partes interesadas. 摘要: 使用有意义的标准确定贫困线是一项复杂的工作。本研究中，我们不使用常规的研究方法。相反，我们采用非参数方法进行比较分析。通过使用菲律宾家庭收入和支出调查，我们估计了国家和地区的Epanechnikov核密度，以期理解2000年至2015年间贫困是如何演变的。结果表明，菲律宾贫困发生率的增加归因于不同的政府减贫计划和国家经济表现的改善。所产生的综合贫困情况促使采取多元化的减贫方法，例如关注农业改革和农村发展、国家工业化政策、支持性贸易政策、金融政策和投资政策、以及稳健的社会保护政策。这一切都需要利益攸关方的协调。